Analysis of Human Resources Competency in Improving Employee Performance of the Cooperative, Micro Business and Trade Service - Mauliyati, Mauliyati; Hidayah, Tamriatin; Dimyati, Muhaimin (PT. AHS Konsultan dan Pelatihan, 2024)
This research aims to determine and analyze employee competency and how to improve employee competency at the Banyuwangi Regency Cooperatives, Micro Enterprises and Trade Department. This research uses a qualitative descriptive approach where data will be analyzed descriptively originating from interviews, notes and the author's observations. The sampling technique in this research used a purposive sampling technique. Data collection techniques in this research are observation, interviews, literature study and documentation. The data analysis approach in this research uses data reduction, data presentation and drawing conclusions. The validity of this research includes data credibility, dependability and confirmability. Based on the results of data analysis, it shows that the competency of employees at the Banyuwangi Regency Cooperatives, Micro Enterprises and Trade Service is good according to their expertise. This can be seen from the suitability of work areas to competencies, proof of competency, support for increasing competency, and overall, the human resource management system in this service is effective in creating good employee performance, contributing to increasing organizational effectiveness. The way to improve employee competency at the Banyuwangi Regency Cooperatives, Micro Enterprises and Trade Department is by providing coaching, evaluating and assessing performance, as well as giving rewards to employees who excel. This holistic approach which includes coaching, evaluation and providing rewards will increase employee competency effectively and efficiently, support human resource development and strengthen the overall performance of the organization.